AN INTERNSHIP IN A MENTAL HEALTH SPECIALIZATION COURSE: AN ACCOUNT OF EXPERIENCE IN A CENTER FOR PSYCHO-SOCIAL ATTENTION - Maria de Lourdes Custódio Duarte; Leandro Barbosa de Pinho; Adriana Inocenti Miasso (Universidade Federal do Paraná, 2011)
This study relates the experience of an internship, mandatory for the title of Specialist in Mental Health Nursing, linked with the post-graduate program of the University of Sao Paulo. The internship was carried out in a Center for Psycho-Social Attention in South Brazil, in the months of June and July 2006. The Centers for Psycho-Social Attention have played their part both as places for the rehabilitation of health service users and as places for the training of students. Evidence was found for both the limitations and potential of the service as an important tool in the psycho-social attention network. The experience of the internship was of great value to the student, health service users and the health team, as all were able to benefit from the exchanges brought about by this encounter.